SELF-EFFICACY, LEARNING STYLES, AND LEARNING DISCIPLINE AS PREDICTORS OF MATHEMATICS ACHIEVEMENT AMONG VOCATIONAL SCHOOL STUDENTS - Sadiyah , Khalimatu; Setiawan , Aldo; Siswanto, Deny Hadi; Fitriyani (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the influence of self-efficacy, learning styles, and learning discipline on students’ mathematics learning outcomes at Muhammadiyah Mlati Vocational School, Sleman. The research employed a quantitative approach using a survey method. The research instrument was a scale that had been validated through expert judgment and tested for its validity and reliability. Data were collected from 150 respondents and analyzed using SPSS-25 through prerequisite tests (normality, multicollinearity, heteroscedasticity, and linearity) and hypothesis testing using regression analysis. The results of the validity and reliability tests indicated that all instrument items were valid and reliable. The data were normally distributed, free from multicollinearity and heteroscedasticity, and met the assumption of linearity among variables. Descriptive analysis showed that the average scores for all variables were relatively high, exceeding 75. Regression analysis revealed that self-efficacy, learning styles, and learning discipline had a significant influence on mathematics learning outcomes, both simultaneously and partially. This study highlights the importance of strengthening students' internal factors in supporting academic achievement, particularly in mathematics learning at the vocational high school level. The findings are expected to serve as a reference for teachers in designing learning strategies that consider students’ individual characteristics